Individual Genetic Contributions to Genital Shape Variation between Drosophila simulans and D. mauritiana. (8th September 2014) - LeVasseur-Viens, Hélène; Moehring, Amanda J.
Abstract : External genitalia are one of the most rapidly evolving morphological features in insects. In the Drosophila melanogaster species subgroup, males possess a nonfertilizing external genital structure, called the posterior lobe, which is highly divergent among even closely related species. A previous study on this subgroup mapped two genomic regions that affect lobe size and four that affect lobe shape differences between D. mauritiana and D. sechellia ; none of the regions affected both size and shape. Here, we investigate whether three of these significant regions also affect lobe size and shape differences between the overlapping species pair D. mauritiana and D. simulans . We found that the same three regions of D. mauritiana, previously shown to affect lobe morphology in a D. sechellia genetic background, also affect lobe morphology in a D. simulans genetic background, with one of the regions affecting both size and shape. Two of the regions also affected morphology when introgressed in the reciprocal direction. The overlap of regions affecting genital morphology within related species pairs indicates either that there is a common underlying genetic basis for variation in genital morphology within this species group or that there are multiple adjacent loci with the potential to influence genital morphology.